PERANAN BANGSAWAN BONE DALAM SISTEM PEMERINTAHAN DARI SWAPRAJA KE KABUPATEN (The Role of Bone Nobleman in The Government System from Swapraja to Regency) - Risma Widiawati (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2018)
Bone Regency as part of South Sulawesi is a very interesting area to discuss. This area is not only part of the history of South Sulawesi, but also a historical flow of South Sulawesi. the existence of nobles who are so attached to the joints of the lives of the people of Bone is still interesting to be examined to this day. Based on this, the article aims to reveal the role of Bone nobility in the swapraja government system to the regency (1950 - 1960). The political development of the government during this period was seen as sufficiently influencing the political dynamics of the government in Bone Regency which continued even today. The method used is the method of historical research with four stages, namely, heuristics, criticism (history), interpretation, and presentation (historiography). The results of the study show that after the transition from swapraja to regency, the role of nobility is still very calculated. But it is no longer like in the period before the transition, where the government was ruled by the king / aristocracy. At this time the level of intelligence is also taken into account. Apart from the fact that the structure of the government is indeed different because the process of appointing head of government is also different. But in general the role of nobility after the transition was not much different, where there were still many nobles holding power. ABSTRAK Kabupaten Bone sebagai bahagian dari Sulawesi Selatan merupakan suatu daerah yang sangat menarik untuk dibicarakan. Daerah ini bukan saja merupakan bagian dari sejarah Sulawesi Selatan, tetapi juga merupakan arus sejarah Sulawesi Selatan. keberadaan bangsawan yang begitu melekat di dalam sendi kehidupan masyarakat Bone masih menarik untuk ditelisik sampai hari ini. Berdasarkan hal tersebut, maka artikel ini bertujuan untuk mengungkapkan tentang peranan bangsawan Bone dalam sistem pemerintahan swapraja ke kabupaten (1950 – 1960). Perkembangan politik dari pemerintahan selama periode ini dipandang cukup mempengaruhi dinamika politik dari pemerintahan di Kabupaten Bone yang berlangsung bahkan sampai sekarang. Metode yang digunakan adalah adalah metode penelitian sejarah dengan empat tahapan yaitu, heuristik, kritik (sejarah), intrepretasi, dan penyajian (historiografi). Hasil penelitian menunjukkan bahwa setelah peralihan dari swapraja ke kabupaten, peranan bangsawan masih sangat diperhitungkan. Namun tidak lagi seperti pada masa sebelum peralihan, di mana pemerintahan dikuasai oleh raja/aristokrasi. Pada masa ini tingkat kecerdasan juga diperhitungkan. Selain karena struktur pemerintahannya memang berbeda juga karena proses pengangkatan kepala pemerintahan juga berbeda. Namun secara umum peran bangsawan setelah masa peralihan tidak jauh berbeda, di mana masih banyak bangsawan yang memegang kekuasaan.